2003
DOI: 10.1023/b:jmsm.0000004002.11278.30
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation and cytocompatibility evaluation of novel soy and sodium caseinate-based membrane biomaterials

Abstract: Soy- and casein-based membranes are newly proposed materials disclosing a combination of properties that might allow for their use in a range of biomedical applications. Two of the most promising applications are drug delivery carrier systems and wound dressing membranes. As for all newly proposed biomaterials, a cytotoxic scanning must be performed as a preliminary step in the process of the determination of the compatibility with biological systems (biocompatibility). In this study, the cytotoxicity of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 17 publications
2
60
0
1
Order By: Relevance
“…Furthermore, it was apparent that tissue treated with Glut/ TA released components more toxic than those resulting from Glut/PGG-treated tissue. Similar studies have been conducted on by-products of TA-treated biomaterials in which their cytotoxic behavior was confirmed [25]. Studies in our laboratory are currently being performed to investigate tissue and organ toxicity of PGG in animal models.…”
Section: Article In Presssupporting
confidence: 53%
“…Furthermore, it was apparent that tissue treated with Glut/ TA released components more toxic than those resulting from Glut/PGG-treated tissue. Similar studies have been conducted on by-products of TA-treated biomaterials in which their cytotoxic behavior was confirmed [25]. Studies in our laboratory are currently being performed to investigate tissue and organ toxicity of PGG in animal models.…”
Section: Article In Presssupporting
confidence: 53%
“…In Figure 7, the cells have elongated polygonal shape and flat surfaces indicating tight cell adhesion to the membranes, and some of the cells have secreted filamentous substances called flagella. 13 The shape of the cells and secretion of flagella indicate that soyprotein fibers are conducive to cell growth and generation of tissues. The biocompatibility and good stability of the soyprotein fibers in physiological pH at 50 and 90 C indicate that the fibers can last for more than 15 days at body temperature allowing for the generation of tissues both in vitro and in vivo.…”
Section: Morphology Of Fibers and Cell Viabilitymentioning
confidence: 99%
“…Attempts were also made to develop biomaterials from soyproteins. 3,13 It was found that thermoplastics made from soyproteins had mechanical and degradation properties suitable for tissue engineering, but no cell culture studies were performed. 3 In another study, membranes were produced by blending chitosan and soyprotein, crosslinked with glutaraldehyde and used as substrates for cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Furthermore, they have potential applications in the medical sector, e.g., as biocompatible wound dressing material or in drug delivery systems. 25,26 Structure of casein micelle Over the years, several models for the casein micelle structure have been published and were intensively discussed in the literature. The first model was introduced by Walstra and suggests the existence of casein sub-micelles with diameters of about 15 nm, linked together by bridges of colloidal calcium phosphate (CCP).…”
Section: Introductionmentioning
confidence: 99%